Gendered Visions. the Art of Contemporary African Women Artists. - Hassan, Salah M.; Désir-Davis, Dorothy; Meyers, Bob; Butler, Diane; Alexis, Florence; Oguibe, Olu; High W. Tesfagiorgis, Frieda (Eritrea : African World Press, 1997)
Tariqua Atnafu, Elsabeth ; Cox, Renée ; Bailey, Xenobia ; Etoundi Essambia , Angèle ; Niati, Houria ; Dimma Poulsen, Etiyé
Vrouwelijke kunstenaars, Afrikaanse hedendaagse kunstenaars
boek